Chemical Synthesis of Modified Oligonucleotides Containing 5′‐Amino‐5′‐Deoxy‐5′‐Hydroxymethylthymidine Residues. Issue 3 (3rd March 2021) - Ohkubo, Akihiro; Muto, Kousuke; Watanabe, Rintaro; Ogata, Daisuke
Abstract: Introduction of cationic modifications into an oligonucleotide can increase its nuclease resistance and duplex‐ or triplex‐forming abilities. In a recent study, we found that the nuclease resistance and RNA binding selectivity of an oligonucleotide containing a 5′‐( R )‐amino‐5′‐deoxy‐5′‐( R )‐hydroxymethylthymidine residue were greater than those of the unmodified oligonucleotide. In this article, we describe the synthesis of 5′‐amino‐5′‐deoxy‐5′‐hydroxymethylthymidine via dihydroxylation of the 5′‐alkene derivative using either of two commercial AD (asymmetric dehydroxylation) mixes or via epoxidation and ring opening. We also provide detailed protocols for the syntheses of oligonucleotides containing 5′‐amino‐5′‐deoxy‐5′‐hydroxymethylthymidine residues. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of 5′‐amino‐5′‐deoxy‐5′‐hydroxymethylthymidine phosphoramidites 9a and 9b Basic Protocol 2 : Synthesis of oligonucleotides 1 and 2 containing 5′‐amino‐5′‐deoxy‐5′‐hydoxymethylthymidine residues (R T and S T)